Characterization and applications of iron oxide nanoparticles synthesized from Phyllanthus emblica fruit extract - Fatima, Easha; Arooj, Iqra; Shahid, Hamna; Aziz, Abida (PLOS ONE, 2024)
Nanotechnology is a treasure trove of diversified themes which are endowed with broad applications. Herein, iron oxide (Fe2O3) nanoparticles were synthesized using Phyllanthus emblica aqueous fruit extract. The UV-Visible spectrum exhibited a surface plasmon resonance peak at 295nm. Fourier Transform Infrared Spectroscopy provided insight into the functional groups responsible for capping. X-ray diffraction analysis authenticated the crystalline nature of nanoparticles, while energy dispersive X-ray spectroscopy divulged that iron and oxygen comprised 54% of the nanoparticles’ weight. Scanning electron microscopy established irregular morphology and agglomeration of nanoparticles. The Fe2O3 nanoparticles validated potent antimicrobial activity against 11 bacterial and 1 fungal isolates. The biggest zone of inhibition (23mm) was measured against S. enterica, whereas the smallest zone of inhibition (12mm) was documented against C. albicans and E. coli. The values for minimum inhibitory concentration ranged between 10 and 15μg/ml for all microbes. Nevertheless, no synergy was exhibited by the nanoparticles with any of the selected antibiotics (Fractional Inhibitory Concentration Index > 1). The photocatalytic dye degradation capability of Fe2O3 nanoparticles was assessed and the observations implied a significant increase in degradation of methyl red although, not of methylene blue. Furthermore, the nanoparticles were in possession of substantial antioxidant (34–38%) and anti-inflammatory (31–38%) capacities. Consequent upon the robust activities of P. emblica-mediated nanoparticles, these can be scrutinized for biomedical and environmental implementations in future.